Habitat diversity of hermit crab Clibanarius longitarsus (de haan) in vellar estuary, Southeast coast of India - R. Elangomathavan, S. Ramesh, S. Sankar Samipillai (Recent Research in Science and Technology, 2009)
The habitat diversity of hermit crab Clibanarius longitarsus was studied in 5 stations of Vellar estuary. This hermit crab was found to occupy the shells of as many as 44 species of gastropods. The abundance of this hermit crab (144/m2- 41/m2) so also the number species of gastropod shells it occupied decreased from the mouth to the upper reaches of estuary (39-11 species). The Shannon diversity (H’log2) was in the range of 4.08-2.64 in stations 1-5. The Margalef species richness showed clear differences between the stations and it varied from 7.52 in station 1 to 2.69 in station 5. The evenness was more in station 1 (0.77) and decreased to 0.65 in station 2 and thereafter it increased in stations 3 and 4 to reach 0.76 in station 5. The taxonomic diversity index decreased from station 1 (75.48) to station 4 (58.59) and increased in station 5 (62.2). The total phylogenetic diversity index which was more in station 1 (1840) decreased through stations 2-5 to reach 660 in station 5. The variation in taxonomic distinctness index increased from station 1 (362.67) to station 3 (468.78). The similarity in species composition of gastropod shells among the stations was in the range of 50.55%-81.73%. In cluster analysis the grouping was quite clear with stations in the lower reaches (stations 1 and 2) forming a group and stations in the middle of the estuary (stations 3 and 4) forming a group to which the station in the upper reaches (station 5) got linked. The cluster analysis and MDS clearly showed the variation in species composition between the stations. The average dissimilarity in species composition between stations 1 and 5 was 63.61%. Gastropod species which contributed to greater percentage of dissimilarity were Cerithidea fluviatilis, Umbonium vestiarium, Pila globosa, Babylonia spirata and Turritella acutangula. The abundance shown as bubble plot clearly showed the decreasing abundance of Cerithidea cingulata, Babylonia spirata and Turritella acutancula from the mouth to the upstream stations. The taxonomic relatedness tests carried out (95% funnel and 95% ellipse) also clearly showed the differences in the habitat diversity of the hermit crab in different stations of Vellar estuary.